Fostering circular economy approach in extractive industry-related study programs – the CIRCEXTIN project. Issue 1 (1st January 2023) - Lutyński, M; Murphy, M; Shogenov, K; Shogenova, A.; Wolf, K-H; Soleymani Shishvan, M; Ortega, M F; García-Martínez, M J; Mora, P; Mazurek, M
Abstract: Extractive industry is an industry where large volumes of waste are generated. Solid waste from mining and quarrying is the second largest stream of waste in European Union. Extractive industry and higher education programs related to it such as mining, mineral engineering, raw materials, and applied earth sciences need to put an emphasis on this context and include this concept in the existing curricula and/or create new study programs or short courses that will include circular economy (CE) approach. In 2020 project CIRCEXTIN funded by the Erasmus+ Strategic partnerships Key Action 2 was started. The objective of this project is to create a strategic partnership between Universities and companies developing a comprehensive training platform that will help to modify existing study programmes related to the extractive industry and knowledge of proper waste management incorporating a circular economy approach. This article presents major assumptions and result of the project as of September 2022.